MOLECULAR DETECTION, TRANSMISSION AND HISTOPATHOLOGICAL STUDIES OF SEED-BORNE FUNGAL INFECTION OF SOYBEAN (GLYCINE MAX (L.) MERILL) - P. K. SAJEESH; M. S. L. RAO; SHAMARAO JAHAGIRDAR (The Bioscan, 2014)
Soybean crop being an oilseed crop has been receiving wider attention in India. Over hundred pathogens are known to affect soybean, of which majority are associated with soybean seeds. Seed borne infection of soybean is very important discouraging factor, which possess a serious problem in seed certification. Seed borne infection of the pathogen is generally detected by conventional methods such as blotter method and agar plate method followed by microscopy. But, these techniques are time consuming and not sensitive. The early detection of seed borne infection by novel molecular techniques like Polymeric Chain Reaction (PCR) using fungal specific primer has tested here. ITS1 and ITS4 were used for the diagnostic purpose of seed-borne fungal infection. Oligonucleotide specific primers targeting the ITS region have been demonstrated to selectively detect several agriculturally important fungi. Further the amplified product sequenced and revealed the sample genome has homology with Cercospora kikuchii and Rhizoctonia bataticola genome. The pathogenic ability of seed borne fungi was proved in transmission studies carried out by seedling symptom test and pot culture studies. Finally the histopathological studies revealed the location of seed borne fungi in the infected soybean seeds. In most of the observations the fungal pathogens were occupied in the pericarp, hilum and endosperm regions.